Heart work : the handbook on the surviving and thriving of cultural and identity centers in higher education - Felix, Alex Romero; Mendoza, Gary Santos; Torres-Baez, Daisy; Davis, Lori Patton (Identity & practice in higher education-student affairs., 2025)
Heart Work: The Handbook on the Survival and Success of Cultural and Identity Centers in Higher Education highlights the experiences of higher education professionals working in these centers. This handbook offers a blend of personal stories and the latest research on cultural and identity centers, building on Dr. Lori Patton Davis' 2010 book, Culture Centers in Higher Education: Perspectives on Identity, Theory, and Practice. Since 2010, these centers have navigated significant challenges, including the global COVID-19 pandemic, and have increased focus on institutional racism. The book delves into the experiences and histories of various cultural and identity centers, including Latinx/e Cultural Centers, Asian, Pacific Islander, Middle Eastern Arab and Desi Cultural Centers, Native American/Indigenous Cultural Centers, Black/African American Cultural Centers, Disability Cultural Centers, Lesbian, Gay, Bisexual, Transgender, Queer+ Centers, and Undocumented Student Resource Centers. In light of recent events affecting minoritized populations, it also covers topics such as evolving practices in cultural/identity centers, university politics, and strategies for practitioners to advance and sustain the Heart Work. Heart Work offers community members - especially practitioners, faculty, and staff in higher education - an understanding of the recent environmental context of cultural and identity centers. As our society evolves, recognizing that identities are not monolithic and embracing intersectionality allows for a deeper understanding of oppression and lived experiences. This handbook aims to bridge the gap by continuing the research and practice of cultural and identity centers in higher education.